Similia similibus: Queer Time in Thomas of Monmouth's Life and Miracles of St William of Norwich. (2nd January 2016) - Wilson, Anna
Abstract : The Life and Miracles of St William of Norwich by Thomas of Monmouth is most notorious as the first example of a ritual murder accusation against a Jewish community in medieval England. However, the overwhelming focus on the Life 's place in a linear history of ever-increasing persecution has obscured the text's own interest in non-linear chronology and temporality. This article draws on recent discussions of temporality in queer theory to show how William's body becomes a point of temporal instability in the Life, and suggests a reconsideration of the figure of the child in queer readings of narrative time.